A Review on Humanized Computational Intelligence - Reis, Cecília (2019)
Computational Intelligence (CI) has three main foundations: Neural Networks, Evolutionary Computation (EC) and Fuzzy Systems (FS). Collaborating systems based on these models have been built and installed in prototypes and successful consumer products. However, creativity still is a main human task, in great part due to the presence of subjective values and psychological / emotional responses in the evaluation of the created objects. In this context the Interactive Evolutionary Computation (IEC), a paradigm in which humans directly intervene in fitness evaluation, is a new direction for CI research. Art, education and engineering are some examples of IEC application domains.